The rs10229583 polymorphism near paired box gene 4 is associated with gestational diabetes mellitus in Chinese women. Issue 1 (January 2018) - Xu, Tianyi; Shi, Yiru; Liu, Jiangbo; Liu, Yun; Zhu, Ailin; Xie, Cui; Zhang, Yan; Chen, Yan; Ren, Lirong
Objective: The rs10229583 polymorphism near paired box gene 4 ( PAX4 ) is associated with insulin resistance and type 2 diabetes. Mutations in the PAX4 gene may be associated with impaired differentiation/development of pancreatic islet beta cells during fetal development and, consequently, a compromised insulin response to high blood glucose. To ascertain whether this polymorphism plays a role in gestational diabetes mellitus (GDM), we investigated the genotypic and allele frequency differences between GDM and normal pregnancies. Methods: A total of 310 GDM and 440 normal pregnancies were evaluated. Allele and genotype frequencies of rs10229583 were determined for all participants with Sanger sequencing and SNaPshot. Association of the allele and genotypes of the single nucleotide polymorphism with the disease was analyzed using Pearson's χ 2 test and OR (odds ratio). Results: The G allele was more frequent in patients with GDM compared with controls (OR = 1.47, 95% confidence interval (CI): 1.12–1.939). The GG genotype frequency of rs10229583 was significantly different between subjects with GDM and normal controls (OR = 1.411, 95% CI: 1.032–1.928). The OR of the GA  +  GG genotype was 3.182 (95% CI: 1.294–7.826) for patients with GDM compared with controls. Conclusion: The present study suggests that rs10229583 is associated with GDM.